2022
DOI: 10.1002/acn3.51526
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor control associates with muscle weakness observed with McArdle sign of multiple sclerosis

Abstract: Objective Multiple Sclerosis (MS) is often accompanied by myelopathy, which may be associated with progressive worsening. A specific finding of MS‐associated myelopathy is McArdle sign, wherein neck flexion is associated with prominent increased limb weakness relative to that detected with neck extension. In this study, we characterized neuromotor control properties of finger extensors in association with the McArdle sign. Methods A custom‐built device was utilized to monitor torque production of the wrist ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…AvgFR appears to follow what has been demonstrated about AMI—inhibited quadriceps and facilitated hamstrings 6 60. Changes in MU recruitment threshold have previously been demonstrated with pathology 37. Similarly, a previous study has shown that intervention in strength training could change the MU recruitment threshold 61.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…AvgFR appears to follow what has been demonstrated about AMI—inhibited quadriceps and facilitated hamstrings 6 60. Changes in MU recruitment threshold have previously been demonstrated with pathology 37. Similarly, a previous study has shown that intervention in strength training could change the MU recruitment threshold 61.…”
Section: Discussionsupporting
confidence: 69%
“… 6 60 Changes in MU recruitment threshold have previously been demonstrated with pathology. 37 Similarly, a previous study has shown that intervention in strength training could change the MU recruitment threshold. 61 However, it is imperative to consider the entire range of recruitment (regression with least squares mean; figures 1–3 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition to internal validation by the development group, the decomposition algorithm has been externally validated against spike triggered averaging technique and further details of the methodology can be found elsewhere ( 33 , 34 ). This technique has been able to determine differences between both healthy and pathological conditions ( 26 , 35 ).…”
Section: Methodsmentioning
confidence: 99%